Flotation of sulfide copper ore from Legnica-Glogow Copper Basin (Poland) in process water of different salinities - Bakalarz, Alicja; Paluchniak, Tomasz (Wroclaw University of Technology, 2025)
The composition of water has a significant impact on the flotation. With the increasing salinity of process waters used at the Division of Concentrator Plant (KGHM Polska Miedz SA), it is necessary to investigate the effect of changes in water composition on the flotation of copper ore components from the Legnica-Glogow Copper Basin area (Poland). In this study, the effect of changing water salinity on the flotation efficiency of copper and organic carbon in sulfide copper ore from the Polkowice Concentrator Plant was investigated. In the study, water taken from the processing plant was used. The mineralization and chloride concentration were 54.5 g/L and 23.46 g/L, respectively. The salinity of the process water was changed by concentrating and diluting water (60, 80, 120, 140%), as well as by adding chloride ions (5 and 10 g/L). Based on the study, it was found that with the increase in mineralization, also the chloride ion con-tent of the water is increased, worse flotation of copper carriers and organic carbon was observed at the cleaning flotation stage. Moreover, it was observed that the more the salinity of the process water is in-creased, the more the efficiency of the rougher flotation improves – while increasing this salinity, the content and loss of Cu in the tailings from this stage decrease. The obtained research results indicate the need to monitor the salinity level of process waters and their composition and perhaps, in the future, the need for modification in this area.
Mining Science, Vol. 32, 2025, s. 87-104
Keywords: mining; geology; geo-engineering